Le voyage de la demoiselle de François de Belleforest vers l’île de Canada - Felice, Maura (Ponti/Ponts, 2021)
The short novel “Cœur genereux d’une damoiselle françoise, exposée avec son mary en une isle deserte de l’Ocean, et comme elle en fut delivrée” belongs to the fifth volume of Histoires tragiques (1572) by François de Belleforest. This tragic story combines several literary traditions of success: the travel literature, the short novel, the adventure and love romances. Our aim is to focus on the courteous imagery and on the topic of the sea in Belleforest, the author who first amplified the edifying plot narrated by the Queen of Navarre.